Design of an Economical Electrical Leak Detector for Rural Cajamarca with Arduino - Castillo Tello, Luis Alberto; Pizan Escalante, Luis Esteban; Carrión Castrejon, Kevnin Jersson; Alaya Peralta, Alicia Fabiana (LACCEI, 2025)
ABSTRACT: In rural areas of Cajamarca, many homes have deficient electrical installations that often go unchecked, leading to electrical leakage, unnecessary energy losses, and serious safety risks. This project presents the design and implementation of a low- cost electrical leakage detector based on Arduino technology, aimed at improving electrical safety and energy efficiency in vulnerable rural households. The prototype was installed in a home in the community of Rinconada, where it successfully detected abnormal current variations and notified the user through visual and acoustic alerts. The methodology applied was applied research with a quantitative approach and experimental design, implemented over a 15-day trial period. Results showed a 30% reduction in electricity consumption and the early detection of hidden wiring issues. The system proved to be affordable, replicable, and user-friendly, making it suitable for widespread adoption in resource-limited settings. Its application not only enhances electrical safety, but also supports household energy savings and contributes to sustainable development in rural Cajamarca.